The Glorious Revolution in America : Documents on the Colonial Crisis of 1689 - Kammen, Michael G.; Leder, Lawrence H.; Hall, Michael G. (Michael Garibaldi) (Book collections on Project MUSE., 1964)
"The Glorious Revolution of 1688, which forced James II from the English throne and established the reign of William and Mary, created a major crisis among the English colonies in America. Following news of England's revolution, a series of rebellions and insurrections erupted in colonial America from Massachusetts to Carolina. Although the upheavals of 1689 were sparked by local grievances in each of the rebellious colonies, there were also general causes for the repudiation of Stuart authority in the New World, fundamental motives and political aspirations which linked the colonies together and in the outcome radically altered the course of colonial development"--Prologue, page 3.